Benefit of monoclonal antibodies in early treatment of COVID-19 after lung transplantation: a retrospective analysis in two centres. Issue 1 (21st July 2022) - Gottlieb, Jens; Kolditz, Martin; Gade, Nils; Welte, Tobias; Kneidinger, Nikolaus
Transplant recipients are at risk for poor outcomes from coronavirus disease 2019 (COVID-19) due to frequent medical comorbidities and presence of immunosuppression. Observational cohort studies suggest that patients after lung transplantation (LTx) with COVID-19 may have higher mortality in comparison to other solid organ transplant recipients. In a US retrospective analysis in the beginning of 2020, 78% of infected transplant patients were hospitalised and 19% died within 28 days [1]. Recently, both mortality and hospitalisation rate have declined in transplanted patients [2] and reduced mortality has been associated with vaccination [3]. Treatment with monoclonal antibodies was associated with improved survival in COVID-19 after lung transplantation (LTx). Age was a negative independent predictor of survival in this cohort of 133 COVID-19 cases after LTx. https://bit.ly/3kx5CBw